The effectiveness and cost-effectiveness of integrating mental health services in primary care in low- and middle-income countries: systematic review. (February 2021) - Cubillos, Leonardo; Bartels, Sophia M.; Torrey, William C.; Naslund, John; Uribe-Restrepo, José Miguel; Gaviola, Chelsea; Díaz, Sergio Castro; John, Deepak T.; Williams, Makeda J.; Cepeda, Magda; Gómez-Restrepo, Carlos; Marsch, Lisa A.
Abstract : Aims and method: This systematic review examines the effectiveness and cost-effectiveness of behavioural health integration into primary healthcare in the management of depression and unhealthy alcohol use in low- and middle-income countries. Following PRISMA guidelines, this review included research that studied patients aged ≥18 years with unhealthy alcohol use and/or depression of any clinical severity. An exploration of the models of integration was used to characterise a typology of behavioural health integration specific for low- and middle-income countries. Results: Fifty-eight articles met inclusion criteria. Studies evidenced increased effectiveness of integrated care over treatment as usual for both conditions. The economic evaluations found increased direct health costs but cost-effective estimates. The included studies used six distinct behavioural health integration models. Clinical implications: Behavioural health integration may yield improved health outcomes, although it may require additional resources. The proposed typology can assist decision-makers to advance the implementation of integrated models.